Absolute generality - Rayo, Agustín; Uzquiano, Gabriel (OUP E-Books., 2006)
Is it possible to quantify over absolutely all there is? Or must all of our quantifiers range over a less-than-all-inclusive domain? It has commonly been thought that the question of absolute generality is intimately connected with the set-theoretic antinomies. But the topic of absolute generality has enjoyed a surge of interest in recent years. It has become increasingly apparent that its ramifications extend well beyond the foundations of set theory. Connections include semantic indeterminacy, logical consequence, higher-order languages, and metaphysics. Rayo and Uzquiano present for the first time a collection of essays on absolute generality. These newly commissioned articles - written by an impressive array of international scholars - draw the reader into the forefront of contemporary research on the subject. The volume represents a variety of approaches to the problem, with some of the contributions arguing for the possibility of all-inclusive quantification and some of them arguing against it. An introduction by the editors draws a helpful map of the philosophical terrain.